Ghana : Enhanced Initiative for Heavily Indebted Poor Countries; Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2004)
This paper highlights Ghana's poverty reduction strategy. The paper also highlights Ghana's performance in observing the requirements for reaching the floating completion point under the framework, including implementation of the national poverty reduction strategy. The updated debt sustainability analysis shows that the amount of debt relief estimated at the decision point will be sufficient to bring the country's debt burden indicators to manageable levels. The sensitivity analysis shows that, after completion point, Ghana's debt sustainability would be robust to moderate country-specific shocks, even of a persistent nature.